2010 43rd Hawaii International Conference on System Sciences 2010
DOI: 10.1109/hicss.2010.72
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Price Forecast Errors on the Economics of Distributed Storage Systems

Abstract: This article analyzes the economic impact of price forecast errors on the optimal operation schedules of distributed (battery) storage systems. The presented simulation model extends a linear optimization model that achieves up to 17% annual savings for a storage system in an environment with dynamically changing electricity prices and under the assumptions of ex-ante known load and price data. The main contribution of this paper is to replace the deterministic load and price curves by imperfect forecasts of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…regression algorithm relies within the extent of the regression function fitting the dataset [10]. Checks are thus imposed into this model by using the Curve fitting algorithm, to make sure that the fitting curve does not exceed to the limit of hampering the whole system [11].…”
Section: B Linear Regression Techniquementioning
confidence: 99%
“…regression algorithm relies within the extent of the regression function fitting the dataset [10]. Checks are thus imposed into this model by using the Curve fitting algorithm, to make sure that the fitting curve does not exceed to the limit of hampering the whole system [11].…”
Section: B Linear Regression Techniquementioning
confidence: 99%
“…The formulation can be modified to include spin and non-spin reserve capacities in practical applications. The operational relations and constraints are shown in (1) to (6).…”
Section: Single Day Bes Scheduling Modelmentioning
confidence: 99%
“…The kW output, losses and stored energy are related by (1); losses and current loading by (2); charging and discharging limits by (3); stored energy limit by (4). Equations (5) and (6) dictate that the available regulation capacity (up and down) are determined by the stored energy at the proceeding hour:…”
Section: Single Day Bes Scheduling Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the distributed storage system has the potential to reduce the electricity cost of the household (Ahlert and Block, 2010). The hydrogen storage concept has been studied from an investment perspective and it was found that the use of hydrogen storage for electricity generation is uneconomical (Taljan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%